Utilization Of Chlorella Pyrenoidosa As A Phytoremediator For Tannery Waste - Adetya, Nais Pinta; Arifin, Uma Fadzilia; Anggriyani, Emiliana; Rachmawati, Laili (Walisongo Journal of Chemistry, 2024)
This study aims to analyze the effect of phytoremediation on the bioremoval of COD, ammonia, and Cr (VI) from tannery wastewater and examine its effect on the growth of Chlorella populations. The research method consisted of two stages: first, preparation of liquid waste media. The second is culturing pure cultures followed by microalgae cultivation using leather tanning liquid waste media with a concentration variation of 0%, 10%, 20%, and 30% v/v. Filtrate samples after harvest were analyzed for COD, ammonia, and Cr (VI). The results obtained in this study show that Chlorella can grow in tanning waste media. The highest exponential phase occurs at a concentration of 20% with a growth rate of 0.557. Tannery liquid waste contains inorganic minerals utilized by Chlorella pyrenoidosa cells for growth. Cultivation of Chlorella pyrenoidosa can reduce leather tanning liquid waste parameters, namely COD, ammonia, and Cr (VI).